Graphical features of interactive dashboards have little influence on engineering students performing a design task - Hoffenson, Steven; Philippe, Cory; Chen, Zuting; Barrientos, Christian; Yu, Zhongyuan; Chell, Brian; Blackburn, Mark (International journal of human-computer studies, 2023)
This study investigates how interactive dashboards influence decision making by exploring how specific dashboard features impact design task performance, efficiency, understanding, and confidence. An experiment was conducted in which undergraduate student participants were given a design activity and randomly assigned to one of five dashboards, each using the same underlying functions but varying in the visualization features employed. These features include different graphical representations of the design decision inputs and performance outputs. Participants were first asked to use their assigned dashboard to design a catapult system that maximizes launch distance while meeting requirements related to height, weight, and cost. Following the design task, they were asked a series of questions about their experiences with the dashboard and their understanding of the catapult model. A between-subjects analysis then evaluated how the dashboard design influenced various outcomes of interest. The results show that students who used the most feature-rich dashboard did not perform objectively better than those with the most feature-sparse dashboard, though their self-reported performance was higher. The performance of female versus male participants was also compared, with no significant differences found. The findings support the notion that dashboards should be designed with minimal features to convey the necessary information, and they also point out the disconnect between objective performance and user-assessed performance with interactive dashboards. •Interactive dashboard designers face choices in how they display information.•Experiment investigates how dashboard features affect design performance.•Graphical features did not lead to improved performance over numbers only.•Visual display of system outcomes led to improved performance on design task.•Substantial disconnects were seen between perceived and actual performance.